Rod-like micelles of octadecyltrimethylammonium bromide and their freezing upon solubilised styrene polymerisation. Issue 96 (30th September 2016) - Zhao, Jianxi; Yu, Hongbin; Deng, Shenglu
Abstract : C18 TABr formed rod-like micelles in ethanol/water (10/90 wt%) with the assistance of SNphs and styrene was then solubilised and polymerised in situ, by which means the mono-dispersed, rod-like micelles were frozen. Abstract : The association of octadecyltrimethylammonium bromide (C18 TABr) in ethanol/water (10/90 wt%) solvent has been studied using light-scattering measurements. With the help of sodium 2-naphthalenesulfonate (SNphs), C18 TABr formed rod-like micelles. Styrene was solubilised into the templating C18 TABr micelles with a mole ratio of SNphs to surfactant ( n SNphs / n C18TABr ) of 0.5, which was examined by dynamic light-scattering (DLS) and UV-spectral measurements. Then the solubilised styrene was polymerised in situ . Dilution experiments were performed to test the freezing effect. It was found that the amount of solubilising styrene, represented as the mole ratio of styrene to surfactant ( n st / n surf ), should be greater than 2.7 so as to achieve a good freezing effect. In the case of n st / n surf = 4.4, well-frozen rod-like micelles were obtained and their morphologies were evinced by TEM images. These frozen micelles were stable even in the 400% dilution test.